Tunable optical parametric oscillator based on ZnGeP2 crystal for greenhouse gas remote sensing systems - Yudin, N. N.; Zinoviev, M. M.; Podzyvalov, S. N.; Kuznetsov, V. S.; Slyunko, E. S.; Lysenko, A. B.; Kalsin, A. Yu.; Gabdrakhmanov, A. Sh.; Yakovlev, S. V.; Sadovnikov, S. A.; Romanovskii, O. A.; Baalbaki, H. (Frontiers in Physics, 2024)
This work is devoted to the development of a compact source of coherent radiation with frequency-energy characteristics and a spectral generation range that allows remote determination of background concentrations of greenhouse gases in the atmosphere. The aim of this work was to create a frequency parametric converter based on ZGP, pumped by Ho:YAG laser radiation. For use as a source in a mobile lidar for remote determination of the concentration of greenhouse gases in the atmosphere. In the course of the research, a layout of an Optical parametric oscillator OPO based on a ZGP crystal with Ho:YAG laser radiation pumping was developed. The system's continuous failurefree operation time was 1.5 hours at a pulse repetition rate of 10 kHz and a pulse energy of the generated radiation of 0.08 mJ. The tuning range of the OPO was from 3.3 to 5 μm when using a Lyot filter. The losses from the average generation power when the Lyot filter was introduced into the resonator were 30%. At the same time, it was possible to achieve a linewidth of the generated radiation of 0.7 nm. The divergence of the generated radiation did not exceed 1.5 mrad.The absorption spectrum of gases CO2, CH4, N2O, CO in a gas cell was simulated for the entire generation range of the ZnGeP2-based OPO. As a result of the simulation, the most intense absorption lines of gases CO2, CH4, N2O, CO in the OPO tuning range were revealed, the central wavelengths of the absorption lines and their spectral width were determined.